SPECIFIC AND STRUCTURE OF CONFLICT IN PLAYS IS G.IBSEN «BRAND» AND V.VINNICHENCO «PROPHET» - Pascevich, N. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The problem of interliterature reception is explored in the article, that is examined on the basis of structure and specific of conflict in plays G.Ibsen «Brand» and V. Vynnychenko «Prorok».